A spring aborted : how authoritarianism violates women's rights in the Arab world - Sidani, Yusuf (Bingley, U.K. : Emerald Publishing Limited, 2019)
The Arab Spring uprisings were not about gender; these were uprisings demanding rights for all. Yet, they presented a rare opportunity for women to let themselves be heard. And, from being some of the most memorable and lasting leaders of these revolutionary protests, female activists were particularly targeted by many regimes. In A Spring Aborted: How Authoritarianism Violates Women's Rights in the Arab World, leadership expert Yusuf Sidani tracks the contributions of female activists, the reasons for the Arab Spring, and the abuse these leaders suffered. Including analysis of protests across Sudan, Egypt, Syria, Yemen, and Tunisia, Sidani looks at the aims of the protests, and the impact, evaluating whether the changes brought about were deep enough to disrupt governance structures. Finally, Sidani explores how the Arab Spring has been hijacked. From deep divisions among the allies who shaped the Arab Spring, to sheer force and brutality, Sidani analyses the causes of the Spring's disintegration.
Preface -- 1. Women of the Arab Spring -- 2. Why the Arab Spring? -- 3. Women, honor, and sexual violence -- 4. Feminism and the Arab Spring -- Conclusion: final words - "Arab Spring" or "Arab Autumn"?
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Authoritarianism -- Social aspects -- Arab countries; Women political activists -- Arab countries; Arab Spring, 2010- -- Social aspects; Political Science -- Political Ideologies / Fascism & Totalitarianism; Political structures: totalitarianism & dictatorship